Corporate Innovation and Competitive Environment - Huse,Morten; Neubaum,Donald; Gabrielsson,Jonas (International Entrepreneurship and Management Journal, 2005)
Empirical studies have shown that the characteristics of the competitive environment influence the corporate innovation activities of U.S. firms. This study attempts to internationalize these studies in two ways. First, it examines the environment-corporate innovation relationship in Norwegian manufacturing firms. Second, it examines how the firms' corporate innovation activities are influenced by their international activities. Results indicate that environment and internationalization are positively related to corporate innovation, but models developed using U.S. firms may not be generalizable to firms from other countries.
Keywords: Strategy & Entrepreneurship